Effect of Composite Action on the Strength of Wood Roofs. (16th March 2015) - Campos Varela, Ivan A.; Gerstle, Walter H.; Dwyer, Stephen
Abstract : Engineering certification for the installation of solar photovoltaic modules on wood roofs is often denied because existing wood roofs do not meet current building codes. Rather than requiring expensive structural retrofits, we desire to show that many roofs are actually sufficiently strong if the effect of composite action produced by joist-sheathing interaction is considered. In a series of laboratory experiments using a limited number of two-by-four wood joists with and without sheathing panels, conventionally sheathed stud-grade joists, surprisingly, exhibited between 18% and 63% higher nominal strength than similar bare joists. To explain this strength increase, a simple model was developed to predict the strengths of the nailed partially composite sections, but the model only justifies a 1.4% to 3.8% increase in bending strength of joists with an allowable bending strength of 1000 psi. More testing is indicated to resolve this discrepancy between laboratory results and analytical modeling results. In addition to elucidating nonlinear partial composite behavior of existing roof systems, this paper shows that, with minor changes in roof framing practices, strength increases of 70% or more are achievable, compared to the strengths of conventionally sheathed joists.